May Gender or Ethnicity Affect Delta Over Baseline Values Obtained by 13-C Urea Breath Test? - Petruzziello, Carmine; Sinatti, Dario; Gnarra, Maria; Migneco, Alessio; Tesori, Valentina; Graziani, Cristina; Gasbarrini, Antonio; Franceschi, Francesco; Ojetti, Veronica (Reviews on Recent Clinical Trials, 2017)
Introduction: 13C-urea breath test (UBT) is a non-invasive test for detecting active H. pylori infection. Previous studies showed a correlation of delta over baseline (DOB) values with bacterial load, mucosal inflammation and successful eradication. Gender has been shown to affect DOB in children. Aim of our study was to verify whether gender or ethnicity affects DOB in adults. Patients and Methods: We retrospectively analyzed data of 2922 patients (1024M/1898F mean age 47±15 years) that underwent UBT in our outpatient unit, from October 2015 to October 2016. Patients were divided based on gender and ethnicity; mean DOB values were then compared. Results: 686 pts (23.4%, 258M/428F, mean age 45±17 years) of 2922 pts showed a positive UBT. Prevalence of H. pylori infection was significantly higher in males compared to females (29% vs 22%; p=0,03). Females showed a significant higher mean DOB (34±25 vs 27,6±22; p=0,008). A total of 2922 UBT were performed during the study period (F:1898, 65%; M: 1024 35%). The prevalence of H. pylori infection is 32% in those from Eastern Countries, 28% in those from South America and 40% in both those coming from Africa and Asia. We found significantly lower DOB values in Italians compared to non-Italian (mean DOB 36±27 vs 69±32; p<0.0001). Conclusion: Our study showed that in our geographic area, prevalence H. pylori infection is higher in males. Moreover, it demonstrates for the first time in our geographic area that adult females show a significantly higher DOB compared to males (p=0,008). Whether this effect may be due to hormonal differences, able to influence gastric emptying, bacterial load, or even the production of urease by H. pylori, merits further investigation.
Keywords: infection